Characteristics and Future Cardiovascular Risk of Patients With Not‐At‐Goal Hypertension in General Practice in France: The AVANT'AGE Study. Issue 4 (7th March 2013) - Zhang, Yi; Lelong, Hélène; Kretz, Sandrine; Agnoletti, Davide; Mourad, Jean‐Jacques; Safar, Michel E.; Blacher, Jacques
<x xml:space="preserve">Abstract</x> Although many studies focus on patients with resistant hypertension, general practitioners (GPs) are more likely to face patients in clinical practice with not‐at‐goal hypertension, whose antihypertensive treatment needs to be modified. However, information regarding such patients is limited. In the present study, 710 GPs in France each included their first 10 not‐at‐goal hypertensive patients, ie, the patients for whom they decided to modify antihypertensive treatment. The study population was composed of 7032 patients (58% men, mean age 62.4±11.5 years). Anthropometric and biologic measurements and clinical data were collected, and vascular age and 10‐year cardiovascular risk were estimated by standard formula. Of 7032 participants, cardiovascular risk factors were prevalent, with 15.1% current smokers, 26.1% obese, 22.8% with diabetes mellitus, 35.1% with dyslipidemia, 12.0% with left ventricular hypertrophy, and 4.9% with renal insufficiency. In the subgroup (n=4697) of patients aged between 30 and 74 years and undergoing primary cardiovascular prevention, vascular age was superior (13 to 28 years) when compared with chronological age in different subgroups. The patients' estimated 10‐year cardiovascular global risk was 25.3±13.6%, with 16.0±10.5% for coronary heart disease, 8.7±6.8% for myocardial infarction, 5.8±4.5% for stroke, and 6.8±6.6% for cardiovascular mortality. Patients with not‐at‐goal hypertension in primary care bear a heavy burden of cardiovascular diseases.